2013 IEEE 29th International Conference on Data Engineering (ICDE) 2013
DOI: 10.1109/icde.2013.6544812
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive radix tree: ARTful indexing for main-memory databases

Abstract: Abstract-Main memory capacities have grown up to a point where most databases fit into RAM. For main-memory database systems, index structure performance is a critical bottleneck. Traditional in-memory data structures like balanced binary search trees are not efficient on modern hardware, because they do not optimally utilize on-CPU caches. Hash tables, also often used for main-memory indexes, are fast but only support point queries.To overcome these shortcomings, we present ART, an adaptive radix tree (trie) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
196
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 306 publications
(200 citation statements)
references
References 23 publications
0
196
0
Order By: Relevance
“…We show that full index creation with radix sort is twice as fast as with quick sort. We also show that ART [20] is up to 3.6 times faster than the AVL-tree in terms of lookup time. We also vary the query selectivity from very high selectivity to medium selectivity and compare the effects.…”
Section: Extending Cracking Algorithmsmentioning
confidence: 77%
See 3 more Smart Citations
“…We show that full index creation with radix sort is twice as fast as with quick sort. We also show that ART [20] is up to 3.6 times faster than the AVL-tree in terms of lookup time. We also vary the query selectivity from very high selectivity to medium selectivity and compare the effects.…”
Section: Extending Cracking Algorithmsmentioning
confidence: 77%
“…[25] Sideways cracking, Covered cracking [15], this paper resp. [25] Sorting: Quick(_insert) sort, Radix(_insert) [12,13] Full index: AVL-tree, B+-tree, ART [1,3,20] Parallel standard cracking P-SC [8,9] Parallel coarse-granular index P-CGI [2] Parallel-chunked standard cracking P-CSC [2] Parallel-chunked vectorized cracking P-CVC Variant of [23] Parallel-chunked coarse-granular index…”
Section: Parallel Cracking Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Askitis and Sinha 33 proposed the HAT-trie that improves the burst trie using cache-conscious hash tables. Other dictionary structures include the adaptive radix tree 34 and the lexicographic tree. 35 In a recent study, Mavlyutov et al 36 concluded that the HAT-trie is an efficient data structure for managing Uniform Resource Identifier (URI) data from comparative experiments involving various data structures; however, they did not evaluate DA dictionaries.…”
Section: Related Workmentioning
confidence: 99%